THE INFLUENCE OF LEADERSHIP, DISCIPLINE, CULTURE ON SCHOOLS IN ULUJAMI PEMALANG REGENCY - Yuli Anggraeni; Rasiman Rasiman; Sumarno Sumarno (Program Studi PGSD Universitas Flores, 2025)
The quality of public elementary schools in Ulujami District, Pemalang Regency has not yet reached optimal standards, partly due to variations in leadership, discipline, and school culture. This study aimed to examine the influence of principal leadership, work discipline, and school culture on school quality in public elementary schools in Ulujami District, Pemalang Regency. The research employed a quantitative design using a correlational approach. The sample consisted of 178 elementary school teachers selected through proportional random sampling. Data were collected using questionnaires measuring variables of principal leadership, work discipline, school culture, and school quality. The findings revealed that principal leadership had a positive and significant effect on school quality by 29.1%, with the vision and mission dimension contributing the most. Work discipline also showed a positive and significant influence on school quality by 38.2%, where the discipline in task implementation dimension had the greatest impact. School culture had a positive and significant effect on school quality by 42.3%, with the democratic culture dimension contributing the most. Furthermore, the combined influence of the three variables significantly affected school quality by 68.8%, with the student learning outcomes dimension showing the strongest impact. These results indicate that principal leadership, work discipline, and school culture significantly enhance school quality and student learning outcomes in public elementary schools in Ulujami District, Pemalang Regency.